Mechanical Property of Beam-to-Column Connection of Steel Structures With All-Steel Buckling-Restrained Braces - Gao, Jinhe; Xi, Jiahuan; Xu, Yuwen; Chen, Baokui; Zhao, Dan; Zhao, Xinquan; Chang, Yi (Frontiers in Materials, 2022)
To avoid brittle fracture and plastic yielding of steel beam-to-column connections under earthquakes, a new beam-to-column connection of steel structures with all-steel buckling restrained braces (BRB) is proposed. The all-steel BRB is connected to the steel beam and column members through pins to form a new connection system. Taking the T-shaped beam-to-column connection steel structure as the research object, two structural types with an all-steel buckling restrained brace installed on one side (S-type) and two sides (D-type) are considered. Theoretical equations of the connection system's initial stiffness and yield load are derived through the mechanical models. The yield load, main strain distribution, energy dissipation, and stiffness of the connection system are investigated through quasi-static tests to verify the connection system's seismic performance. The tests revealed that the proposed new connection system is capable of achieving a stable hysteresis behavior. At the end of loading, the member is not damaged, and the plastic deformation is concentrated in the plastic energy dissipating replaceable buckling restrained brace, and the beam and column basically remain elastic. The proposed equations approximately estimated the load response of the proposed connection system. The results show that the damage mode of this new connection system under seismic loading is BRB yielding, with an elastic response from the beam-column members.